Current Advances in the Sustainable Conversion of 5‐Hydroxymethylfurfural into 2, 5‐Furandicarboxylic Acid. Issue 13 (13th May 2022) - Totaro, Grazia; Sisti, Laura; Marchese, Paola; Colonna, Martino; Romano, Angela; Gioia, Claudio; Vannini, Micaela; Celli, Annamaria
Abstract: 2, 5‐Furandicarboxylic acid (FDCA) is currently considered one of the most relevant bio‐sourced building blocks, representing a fully sustainable competitor for terephthalic acid as well as the main component in green polymers such as poly(ethylene 2, 5‐furandicarboxylate) (PEF). The oxidation of biobased 5‐hydroxymethylfurfural (HMF) represents the most straightforward approach to obtain FDCA, thus attracting the attention of both academia and industries, as testified by Avantium with the creation of a new plant expected to produce 5000 tons per year. Several approaches allow the oxidation of HMF to FDCA. Metal‐mediated homogeneous and heterogeneous catalysis, metal‐free catalysis, electrochemical approaches, light‐mediated procedures, as well as biocatalytic processes share the target to achieve FDCA in high yield and mild conditions. This Review aims to give an up‐to‐date overview of the current developments in the main synthetic pathways to obtain FDCA from HMF, with a specific focus on process sustainability. Abstract : Oxidation strategies : Sustainable approaches to perform the oxidation of biobased 5‐hydroxymethylfurfural (HMF) into 2, 5‐furandicarboxylic acid (FDCA) are considered and reviewed. In particular, the most recent developments in metal‐mediated heterogeneous catalysis, metal‐free catalysis, electrochemical approaches, light‐mediated procedure, as well as enzymatic and biocatalytic processes are reported and discussed.